Farmers Perception about Plant Protection Skills of Field Extension Workers in Enhancing Tomato Production of District Peshawar, Khyber Pakhtunkhwa, Pakistan - Muhammad Zafarullah Khan; Saddam Hussain; Urooba Pervaiz; Ayesha Khan; Tariq Ahmad; Shah Saud; Mehmood Iqbal (Research and Social Study Institute, 2022)
This study analyzed farmers’ perception about plant protection skills of extension workers in increasing the tomato production of District Peshawar, Khyber Pakhtunkhwa Pakistan. For the present study two villages each were taken purposively from three union councils of Town 2 of District Peshawar for data collection. Well-structured interview schedule was employed for data collection and SPSS V.20 software was used for analysis. Results were presented as simple percentages while Likert scale was used for ranking purpose. Above 40 years tomato growers were 30% where 37% owned 1-2 acres of land and majority (76.9%) tomato growers were literate. About 31% tomato growers were getting Pakistani Rupees 40,000-80,000 per season and maximum (52%) tomato growers were getting production from local varieties of almost 3,001-6,000 kg/acre. Farmers' perceptions about extension workers' familiarity for selection of economical methods for pest control was ranked first with highest mean value 3.1587 with SD 1.15421 and symptoms of insect/ pest infestation disease and their causes identification was ranked 2nd with the mean value of 3.0337 and SD 1.18925, while life stages of tomato insects identification was ranked 3rd with the mean value of 2.6635 and SD 1.20875 and knowledge of adverse environmental effects of pesticides was ranked 4th with lower mean value of 2.5096 and SD 1.34412. Knowledge about biological control of pest was ranked 5th with the lowest mean value of 2.1635 and SD 1.11737. Extension worker plays a significant role in enhancing the production of tomatoes as highly significant association existed between average yield of tomato and skills of extension worker regarding plant protection skills. The study recommends that extension personnel should visit tomato growers regularly at each stage to address their plant protection issues and recommend weather suitability of tomato varieties for higher production by protecting the crop from the damage of insects. Local agriculture programs should be broadcasted on FM channel and pamphlets may be used for creating awareness regarding tomato protection point of view.